Volatile organic compounds of Metarhizium brunneum influence the efficacy of entomopathogenic nematodes in insect control - Esam Hummadi (Biological Control, 2021)
The entomopathogenic fungus (EPF) Metarhizium brunneum occupies the same ecological niche as entomopathogenic nematodes (EPN), with both competing for insects as a food source in the rhizosphere. Interactions between these biocontrol agents can be antagonistic or synergistic. To better understand these interactions, this study focussed on investigating the effect of M. brunneum volatile organic compounds (VOCs), 1-octen-3-ol and 3-octanone, on EPN survival and behaviour. These VOCs proved to be highly toxic to the infective juveniles (IJs) of the EPN Steinernema carpocapsae, Steinernema feltiae and Heterorhabditis bacteriophora with mortality being dose dependent. Chemotaxis studies of H. bacteriophora IJs in Pluronic F127 gel revealed significant preference for the VOCs compared with controls for all tested concentrations. The VOCs also impacted on the test insects in a dose-dependent manner with 3-octanone being more toxic to Galleria mellonella, Cydia splendana and Curculio elephas larvae than 1-octen-3-ol. Mortality of C. splendana and G. mellonella larvae was significantly higher when exposed to relatively high doses (>25%) of 3-octanone. Lower doses of 3-octanone and 1-octen-3-ol immobilised test insects, which recovered after exposure to fresh air for 2 hrs. In depth studies on H. bacteriophora showed that exposure of IJs to > 10% concentration of 3-octanone or 1-octen-3-ol negatively affected infectivity whereas exposure to lower doses (0.1%, 0.01%) had no effect. The VOCs affected IJs, reducing penetration efficacy and the number of generations inside G. mellonella but they failed to inhibit the bacterial symbiont, Photorhabdus kayaii. The ecological significance of VOCs and how they could influence EPF-EPN insect interactions is discussed.